Community aged care: Guidelines for a palliative approach - Toye, Christine; Abbey, J.; Currow, D.; Hegarty, M.; Holloway, Kristi; Tieman, J. (Wiley, 2012)
A palliative approach promotes quality of life for older people with life limiting illnesses or who are becoming increasingly frail; it is a holistic approach addressing physical, psychosocial, and spiritual needs and can be provided by the usual care team. This project provided guidance for delivering a palliative approach for older people in the community setting. The project was funded by the Australian Government Department of Health and Ageing.